Information Technology and Managing Quality Education 9th IFIP WG 3.7 Conference on Information Technology in Educational Management, ITEM 2010, Kasane, Botswana, July 26-30, 2010, Revised Selected Papers - Tatnall, Arthur; Kereteletswe, Omponye Coach; Visscher, Adrie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed post-proceedings of the 9th IFIP WG 3.7 Conference on Information Technology in Educational Management, ITEM 2010, held in Kasane, Botswana, in July 2010. The 22 revised full papers presented were carefully reviewed and selected. The papers cover a wide range of topics addressing the utilization of ICT at different levels of education from primary education to higher education, such as identifying and satisfying learning needs, strategical management, school management information systems, open source software, and the relationship between ICT and organizational performance.
Keywords: Computer science; Education; Computer Science; Computers and Education; Computers and Society; User Interfaces and Human Computer Interaction